2016
DOI: 10.1016/j.pharep.2015.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced pretreatment CD25 expression on peripheral blood CD4+ T cell predicts shortened survival in acute myeloid leukemia patients receiving induction chemotherapy

Abstract: Our data indicate that quantification of CD25 expression on peripheral blood CD4+ T cells could become a novel, easily accessible method of shortened survival prognostication of AML patients subjected to standard cytotoxic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…These beads are particles labeled with a mixture of fluorochromes at different fluorescent intensity levels (23). In addition, rainbow beads allow setting a fixed output value (target MFI) for each fluorescent channel (3,33,34). In addition, rainbow beads allow setting a fixed output value (target MFI) for each fluorescent channel (3,33,34).…”
Section: Flow Cytometers Standardizationmentioning
confidence: 99%
See 3 more Smart Citations
“…These beads are particles labeled with a mixture of fluorochromes at different fluorescent intensity levels (23). In addition, rainbow beads allow setting a fixed output value (target MFI) for each fluorescent channel (3,33,34). In addition, rainbow beads allow setting a fixed output value (target MFI) for each fluorescent channel (3,33,34).…”
Section: Flow Cytometers Standardizationmentioning
confidence: 99%
“…By this principle, designated MESF beads can be used to create a standard curve of MFI versus MESF values can translate MFI to more universal MESF units. Furthermore, the two methodologies can be combined to receive the best inter-assay precision; first setting target MFI with the aid of the rainbow beads followed by conversion of the MFI values of the sample to universal MESF values (34). It should be noted that it is recommended to further calibrate the assay with cells or particles labeled with a known number of fluorochromes (1,2,5,36).…”
Section: Flow Cytometers Standardizationmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these studies demonstrated a significant higher percentage of Tregs than the control and the antileukemic activity of T cells was negatively correlated with Tregs (Schick et al, 2013). Furthermore, another study established a link between the presence of elevated CD25 levels on T helper cells and reduced survival rate (Bołkun et al, 2016). These studies pay the attention towards the Tregs as a factor implicated in impairment of T cell function and antitumor response either directly or indirectly (Wilke et al, 2011).…”
Section: Regulatory T Cells (Tregs)mentioning
confidence: 97%